Luteolibacter marinus sp. nov., a novel bacterium in the family Verrucomicrobiaceae, isolated from marine sediment. Issue 10 (18th October 2022) - Xie, Feilu; Zhu, Suting; Guo, Chaobo; Liu, Xinyu; He, Shan; Zhang, Weiyan
Abstract : A Gram-negative, rod-shaped, non-motile and strictly aerobic bacterium, designated NBU1238 T, was isolated from marine sediment sampled on Meishan Island located in the East China Sea. Strain NBU1238 T was able to grow optimally at 28–32 °C, at pH 7.5 and with no NaCl. Catalase and oxidase activities, H2 S production and hydrolysis of Tweens 40 and 60 were positive. Methyl red reaction, Voges–Proskauer test and hydrolysis of starch, casein and Tweens 20 and 80 were negative. The major cellular fatty acids were iso-C14 : 0, C16 : 0, C16 : 1  ω 9 c and C14 : 0 . The only respiratory quinone was menaquinone-9. The major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylmethylethanolamine. The 16S rRNA gene sequence of strain NBU1238 T showed 95.6, 95.6, 94.8 and 93.8% sequence similarity to Luteolibacter flavescens GKX T, Luteolibacter luteus G-1-1-1 T, Luteolibacter arcticus MC 3726 T and Luteolibacter pohnpeiensis A4T-83 T, respectively. Phylogenetic analyses indicated that strain NBU1238 T clustered with the genus Luteolibacter and was closely related to strains L. flavescens GKX T, L. arcticus MC 3726 T and L. luteus G-1-1-1 T . The average nucleotide identity and digital DNA–DNA hybridization values between strain NBU1238 T and related species of genus Luteolibacter were well below the threshold limit for prokaryotic species delineation. The DNA G+C content of the genomic DNA was 65.0 mol%. Based on its phenotypic, chemotaxonomic and genotypic data, strain NBU1238 T is considered to be a representative of a novel species in the genus Luteolibacter, for which the name Luteolibacter marinus sp. nov. is proposed. The type strain is NBU1238 T (=KCTC 82227 T =MCCC 1K04772 T ).